Dispersal limitation and weaker stabilizing mechanisms mediate loss of diversity with edge effects in forest fragments. (12th March 2021) - Krishnadas, Meghna; Stump, Simon Maccracken
Abstract: Whether fragmented ecosystems can maintain diversity is a key ecological question. The ability of fragmented forests to support diversity is determined by both landscape‐scale metapopulation dynamics and within‐patch mechanisms that govern species coexistence. Within‐patch dynamics can be affected by proximity to forest edges. Edge effects on abiotic and biotic processes can alter species' performance and species interactions, but it is unclear how edge effects bear upon the long‐term ability of fragmented forests to maintain diversity. We apply modern coexistence theory as a framework to predict the impact of edge effects on species coexistence. Using field data for a tropical tree community, we parameterized a spatially explicit simulation model to quantify how habitat and density dependence during seedling establishment affect diversity of later life stages. We matched simulated future communities to observed patterns of diversity and community structure for established seedlings and adults, coupled with sensitivity analysis of simulated effects. We found that early recruitment dynamics contributed to community structure at older life stages, corroborating empirical work on the importance of early life‐stage dynamics for diversity. Edge effects reduced the diversity maintained in patches. The progressive loss of diversity was not due to changes in relative competitive ability (fitness differences), but due to weaker stabilization via density‐dependent seed mortality. Results were robust to wide changes in the absolute values of model parameters, suggesting that variation in the strength of individual processes did not change their relative importance for diversity. Synthesis . Weakening of stabilizing processes that promote species self‐limitation in ecological communities could compromise the ability of habitat fragments to maintain diversity. Quantifying the relative importance of intraspecific versus interspecific interactions—to assess stabilizing mechanisms and fitness differences—can help evaluate when habitat amount versus quality plays a larger role in maintaining diversity of fragments. Abstract : Weakening of stabilizing processes that promote species self‐limitation in ecological communities could compromise the ability of habitat fragments to maintain diversity. Quantifying the relative importance of intraspecific versus interspecific interactions—to assess stabilizing mechanisms and fitness differences—can help evaluate when habitat amount versus quality plays a larger role in maintaining diversity of fragments.